A Korean case of neurofibromatosis type 1 with an exonic splicing enhancer site mutation - Park, Sangwook; Sohn, Young Bae; Chung, In-Soon; Hong, Ji-Hee; Jung, Eun-Jung; Jeong, Seon-Yong; Jin, Hyun-Seok (Journal of genetic medicine, 2014)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disease characterized by neurological, cutaneous, andophthalmological manifestations. A 33-year-old woman with typical symptoms of NF1 visited Ajou University Hospital. Screening of the whole-messenger RNA region of NF1 at the complementary DNA level by polymerase chain reaction-directsequencing confirmed the presence of an NF1 mutation at the genomic level. The mutation analysis revealed an in-frameskipping of exon 46 (c.6757_6858del) caused by a point mutation (c. 6792C>A) in exon 46. In this report, we have describedthe first Korean case of a proband with NF1 that carries an allele with an exon 46 deletion caused by an exonic splicingenhancer site mutation, leading to the skipping of the whole of exon 46 (c.6757_6858del). KCI Citation Count: 0